Lucky Jim - Amis, Kingsley; Gertrude Clarke Whittall Poetry and Literature Fund.; Archive of Recorded Poetry and Literature (Library of Congress) (London: Victoe, 1958)
Mr. Kingsley reads thirteen poems from his collected work, A case of samples; chapter six from his novel, Lucky Jim; chapter ten from his novel, That uncertain feeling; and chapter twelve from his novel, I like it here.
Masters -- The last war -- The value of suffering -- Lucky Jim, chapter 6 -- A bookshop idyll -- The garden -- Autobiographical fragment -- That uncertain feeling, chapter 10 -- The triumph of time [two readings] -- On staying still -- Departure -- Against romanticism -- I like it here, chapter 12 -- A dream of fair women -- A song of experience -- Romance.
Sponsored by the Gertrude Clarke Whittall Poetry and Literature Fund, Library of Congress, Washington, D.C.
Recorded for the Archive of Recorded Poetry and Literature.
Literary recordings, rev., enl. ed.
Recorded Oct. 13, 1958, in the Coolidge Auditorium at the Library of Congress in Washington, D.C.
Preservation master.